Guía etnobotánica de las plantas medicinales de los mercados de Latacunga, provincia de Cotopaxi. - Pachacama Villagrán, Andrea Joselyn (2020)
In the present research project, the study of plants marketed in the markets of the city of Latacunga, Cotopaxi Province where intangible knowledge and collective memories could be documented that traders in the markets of "El Leap", "La Merced" and "Wholesale" Market. The objectives set out in the research project were to describe the origin of the use of the plants, by bibliographic and field review, where through surveys the traders agreed that it was by family tradition that they obtained the Knowledge. It was concrete that the use of plants for medicinal purposes has a lot of history and has occurred since time immemorial, although unfortunately today, it is not very important. In the exploratory exits the species of the markets were collected and identified and processed to deposit them in the herbal is applied to the Technical University of Cotopaxi (UTCEC). 41 botanical families and 158 species were recorded, the most commonly used families were Asteraceae with 14 uses, Lamiaceae with 11 uses, Fabaceae and Amaranthaceae with 5 uses, Poaceae with 4 uses and the remaining families of 3 to 1 use. Uses were grouped into fields such as general conditions, digestive system, respiratory system, aesthetic beauty, specific diseases, external wounds, reproductive organs, circulatory, nervous and urinary systems, finally disorders of the Dream. The fields on uses that were most relevant within the markets were general conditions, such as curing bad air, reducing stress, headaches, digestive system, such as stomach pains, inflammation of the kidneys, kidney system treatment to remove cough, flu, colds and circulatory system, especially for heart problems and blood pressure. An ethnobotanical guide was developed with the best-selling families and species in the markets, which also includes scientific name, common name, medicinal use, origin and distribution and witness show of the botanical collection.